Peanut (Arachis hypogaea) Shells Extract and Apis dorsata Honey Reduce Matrix Metalloproteinase-3 in Monosodium Iodoacetate-Induced Osteoarthritic Rats - Bella Stevanny; Tungki Pratama Umar; Junoretta Haviva Ernanto; Rachmat Hidayat (Journal of Biomedicine and Translational Research, 2020)
Background: Osteoarthritis is the most common degenerative joint disease worldwide but its treatment can cause serious adverse events. Ethanol extract of peanut shells contains luteolin functioned as its main anti-inflammatory and chondroprotective agent. Apis dorsata honey also contains anti-inflammatory and antioxidant agent, especially from Tualang honey type. Both have the potential to reduce inflammation and prevent articular degradation in osteoarthritis.